Etika Berbicara Bahasa Jawa pada Siswa SMK Muhammadiyah 3 Yogyakarta - Hanif Azmi Al Hafidh; Akhmad Fajar Prasetya (JCOSE Jurnal Bimbingan dan Konseling, 2022)
Students when speaking, the language used is javanese ngoko to speak to teachers and friends at school and rarely use smooth Javanese language or krama inggil language in speaking to teachers, therefore this study was created, the purpose is to find out the ability of students to use the ethics of speaking in Javanese from ngoko language to the language of innocent krama and the ability to change the language of krama lugu into the language of krama inggil, research methods using quantitative descriptive, this means that the research that will be carried out focuses on describing or describing existing phenomena using numbers as a form of interpretation, the results of the study show that the ethics test for speaking Javanese in students of SMK Muhammadiyah 3 Yogyakarta class XI and if in total has a percentage in the good category of 6% and a fairly good one with a percentage obtained of 77% and for the category of less good at 17%, This acquisition can be a reference that the ability of students of SMK Muhammadiyah 3 Yogyakarta in understanding Javanese can be considered quite good, but not good in practice, these results are based on this research process, and the conclusion of the research that can be taken is that students' understanding in the ethics of speaking Javanese requires further learning so that students can practice good Javanese to anyone according to their levels.